2006
DOI: 10.1038/ja.2006.34
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and Pharmacokinetic Studies of Prodrug Esters for the Development of Oral Carbapenem, L-084

Abstract: We discovered an orally active carbapenem, L-084, through pharmacokinetic studies on various prodrug esters of (1R,5S,6S)-). L-084 showed a strong antimicrobial activity against Gram-positive and Gramnegative bacteria and exhibited the highest intestinal absorption among synthesized prodrugs of LJC11,036.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…12) In recent years, the development of new antibiotics has attracted the attention in the clinical realm for the treatment of severe infectious diseases. L-084 is one of several promising candidates for oral administration and is now under clinical trials.…”
Section: Resultsmentioning
confidence: 99%
“…12) In recent years, the development of new antibiotics has attracted the attention in the clinical realm for the treatment of severe infectious diseases. L-084 is one of several promising candidates for oral administration and is now under clinical trials.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, prodrug approaches have been undertaken to overcome the poor oral availability of carbapenems [4]. Some prodrugs have been reported to afford increases in the oral availability of parent carbapenems [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In the early stage of the development of L-084, thiol 1 was prepared from the acetylthio compound 9 according to the above method we previously reported. 28) As for a large-scale production, the oily compound 9 was considered not to be an appropriate precursor, and the second generation precursor, crystalline compound 10, was omitted due to the cost of a metal thiobenzoate (Chart 2). As a more convenient method for the preparation of 1, the introduction of a dithiosulfonate group was investigated.…”
mentioning
confidence: 99%
“…28) Compound 5 was obtained in two steps including cyclization of N-benzhydryl-3-chloro-2-hydroxypropylamine (3) and deprotection of the N-substituent according to the literature (Chart 2). 31,32) Although compound 5 has been well recognized as a useful building block for various bioactive molecules such as antimicrobial agent WQ-2743, 33) antiepileptic Dezinamide 34) and antihypertensive Azelnidipine, 35) it has been suggested that the above two-step procedure for 5 was too expensive to adopt for large-scale production.…”
mentioning
confidence: 99%
See 1 more Smart Citation